Pelatihan 3M Pencegahan Penularan Covid-19 dengan Metode Bercerita untuk Anak Taman Kanan-Kanak Islam Terpadu (TKIT) Miftahussalam - Rohmah, Farida Noor; Rahayu, Setya Putri (Research and Social Study Institute, 2021)
Based on the observations at TKIT Miftahussalam, it was found that students were scheduled to attend school face-to-face once a week. Although limited in number, in fact, there are still some students who are negligent, for example, did not wear masks properly and did not keep their distance and were reluctant to frequently wash their hands with soap. Despite the school's repeated communication of health protocols, some students were still hesitant to put them into effect. The community service was themed